2021
DOI: 10.1002/jia2.25808
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HIV treatment differentiated care uptake during the COVID‐19 pandemic in Zambia: interrupted time series analysis

Abstract: IntroductionDifferentiated service delivery (DSD) models aim to improve the access of human immunodeficiency virus treatment on clients and reduce requirements for facility visits by extending dispensing intervals. With the advent of the COVID‐19 pandemic, minimising client contact with healthcare facilities and other clients, while maintaining treatment continuity and avoiding loss to care, has become more urgent, resulting in efforts to increase DSD uptake. We assessed the extent to which DSD coverage and an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…A national campaign had been initiated to make early contact with all people living with HIV and to provide extended ART refills (up to 6 months) in March and early April 2020. 12 Notably, in the first 3 months of the pandemic in Zambia, and following a large immediate decline in tuberculosis notifications, we found that case numbers either stayed flat or continued to decline among most subgroups and in most provinces. These data have important implications, as even short disruptions in tuberculosis services and transient declines in tuberculosis notifications may result in thousands of additional tuberculosis-related deaths and many new incident tuberculosis cases due to prolonged periods of infectiousness.…”
Section: Discussionmentioning
confidence: 63%
“…A national campaign had been initiated to make early contact with all people living with HIV and to provide extended ART refills (up to 6 months) in March and early April 2020. 12 Notably, in the first 3 months of the pandemic in Zambia, and following a large immediate decline in tuberculosis notifications, we found that case numbers either stayed flat or continued to decline among most subgroups and in most provinces. These data have important implications, as even short disruptions in tuberculosis services and transient declines in tuberculosis notifications may result in thousands of additional tuberculosis-related deaths and many new incident tuberculosis cases due to prolonged periods of infectiousness.…”
Section: Discussionmentioning
confidence: 63%
“…Differentiated service delivery (DSD) may help to minimize the risk of COVID-19 exposure while continuing to meet the healthcare needs of pregnant women and CLWH [30,31]. There was an increased demand for DSD during the pandemic [32], with evidence supporting its non-inferiority compared to the standard of care [33,34]. Dispensing multi-month ART prescriptions, a cornerstone of the DSD framework, can enable individuals to maintain ART adherence without frequent clinic visits, as demonstrated in Tanzania and Namibia [35,36].…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…We collected data from 378 PLHIV at 25 facilities; one of the rural health centres did not have HIV consultations on the day of data collection. A median of 16 PLHIV participated at each facility (IQR: [12][13][14][15][16][17][18][19]. The median age of participants was 41 years (IQR: 32-51 years); 245 (65%) were female.…”
Section: Characteristics Of Participating Plhiv and Enrolment In Diff...mentioning
confidence: 99%
“…However, implementation barriers, including insufficient staff training, lack of dedicated personnel or insufficient support and resources, may prevent the successful implementation and uptake of differentiated ART delivery [14][15][16]. Health emergencies, such as the recent coronavirus (COVID-19) pandemic, can also challenge the HIV care delivery, especially where services are already stretched [17,18]. In this context, DSD can reduce the burden on providers by offering community-and facility-based models of ART delivery with fewer clinic visits [19].…”
Section: Introductionmentioning
confidence: 99%